ELEMENTS OF POWER RELATION IN LITERARY WORK: A FOUCAULDIAN ANALYSIS - Gartika Rahmasari; Iis Kurnia Nurhayati (English Journal Literacy Utama, 2020)
Literary works can be read for pleasure reading because they can be a source of entertainment that contains interesting stories or plots. On the other hand, we can also find interesting situation or condition that happens to the characters in a novel, for example power relation. This study aims to examine the power relationship that occurs between two characters named Gustad Nobel dan Ghulam Mohamed in a novel by Rohinton Mistry entitled Such a LongJourney (Mistry, 1991) utilizing power relation theory nu Foucault (2002). This study applies descriptive research method in analyzing the power relation occurred. As a result, the power relation between Gustad Nobel and Ghulam Mohamed occurred in an institution of